The metaverse of violence - Pascali, Michelangelo (Frontiers in Sociology, 2024)
The metaverse appears to be a composite concept and a complex environment from an ontological perspective and from a purely dimensional point of view. Exploring its defining features not only allows one to identify the nature and the effects of the social relations existing therein, but also influences the legal reading of what it contains and produces. The same holds true for violent phenomena, regardless of whether or not they fall within the framework of organized crime. Bringing to light the peculiar characteristics of the metaverse – for which the dichotomy between “real” and “virtual” sounds outdated –, this article emphasizes the urgency to rethink the traditional forms of interpretation and design of preventive and repressive measures to counter deviant and illegal phenomena of a violent nature.